Investigation of effects caused by water disinfection byproduct (3-Amino-9 ethylcarbazole) on zebrafish using toxicological tests and gene expression analysis - Balogh, Erna; Berta, Roberta; Gazsi, Gyöngyi; Garai, Edina; Reining, Márta; Urbányi, Béla; Bakos, Katalin; Csenki, Zsolt (Animal welfare, Ethology and Housing Systems (AWETH), 2019)
The aim of this study was the investigation of toxic effects of 3-Amino-9 ethylcarbazole (3A9EC) water disinfection byproduct. Tests were carried out according to the modified OECD (Organisation for Economic Cooperation and Development) guideline (No. 236) in order to detect the acute and sub-chronic toxic effects of 3A9EC.At the end of exposure, LC50 and LC10 values for embryo mortality were determined.Next, a subchronic assay of 33 days was conducted to study the lethal and sub-lethal effects of 3A9EC on the early life stage of zebrafish. On the basis of acute test results, embryos were exposed to two test concentrations below the 72h LC10. At the end of the test, only those individuals survived which were treated with the lower concentrations of 3A9EC. Treated embryos showed developmental malfunctions, differences in size and depigmentation compared to the control group.To observe vascular and nervous system effects, experiments were conducted on three transgenic zebrafish lines. Impairments were only detected in 72 hours post fertilization (hpf) larvae.However results provide complex information on the toxic effects of 3A9EC, it seems that the substance could be potentially harmful to living organisms including humans, so further experiments are needed.
Keywords: zebrafish; toxikology; water disinfection byproduct